Maximum Likelihood Estimation of the Friedman Consumption Function - Singh, Balvir (The Review of Economics and Statistics, 1975)
Cramer, H., Mathematical Methods of Statistics (Princeton: Princeton University Press, 1946). Pesaran, M. H., Alternative Econometric Approach to the Permanent Income Hypothesis: an International Comparison: A Comment, this REVIEW, LV (1973), 259-261. Rao, B. B., Alternative Econometric Approach to the Permanent Income Hypothesis: An International Comparison, this REVIEW, LV (1973), 261. Singh, B., Maximum Likelihood Estimation of the Friedman Consumption Function, this REVIEW, LVII (Feb. 1975). Singh, B. and H. Drost, Alternative Econometric Approach to the Permanent Income Hypothesis: an International Comparison, this REVIEW, LIII (Nov. 1971), 326-334. Tukey, J. W. Components in Regression. Biometrics (1951). Willassen, Y., Specification and estimation of the original P.I.H. (Working Paper) 1972. Wold, H., Nonlinear Estimation by Iterative Least Square Procedures. Festschrift for J. Neyman. Wiley and Sons, 1966.